Prepartum Anemia and Risk of Postpartum Hemorrhage: A Meta-Analysis and Brief Review - Hannah Glonnegger MD; Michael M. Glenzer MPH; Lian Lancaster MD; Richard F.W. Barnes PhD; Annette von Drygalski MD, PharmD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Postpartum hemorrhage (PPH) is responsible for 30% to 50% of maternal deaths. There is conflicting evidence if prepartum anemia facilitates PPH. A comprehensive analysis of studies describing their relation is missing. An extensive database search was conducted applying the terms “anemia” OR “hemoglobin” AND “postpartum hemorrhage.” We used a random-effects meta-analysis model to estimate an overall odds ratio (OR) for PPH and prepartum anemia, separating studies that were conformant and non-conformant with the World Health Organization (WHO) definitions for anemia. The search yielded 2519 studies, and 46 were appropriate for analysis. The meta-analyses of WHO-conformant ( n  = 22) and non-conformant ( n  = 24) studies showed that the risk of PPH was increased when anemia was present. The ORs were 1.45 (CL: 1.23-1.71) for WHO-conformant studies, 2.88 (CL: 1.38-6.02) for studies applying lower thresholds for anemia, and 3.28 (CL: 2.08-5.19) for undefined anemia thresholds. PPH risk appeared to increase with lower anemia thresholds. Prepartum anemia is associated with an increased risk of PPH, an observation that is important regarding improved anemia correction strategies such as iron supplementation.